Methylphenidate causes cytotoxicity on photoreceptor cells via autophagy. (January 2021) - Kong, N; Bao, Y; Zhao, H; Kang, X; Tai, X; Shen, Y
Methylphenidate (MPH) is used as the first-line treatment for attention-deficit hyperactivity disorder. However, there are concerns that this treatment may be associated with increased risk of retinal damage. This study was to investigate cytotoxicity of MPH on photoreceptor cells and explore its underlying mechanisms. MPH-caused cell toxicity was established in 661 W cells. Cytotoxicity was evaluated by 3-(4, 5-dimethylthiazol)-2, 5-diphenyltetrazolium-bromid and lactate dehydrogenase assays. Oxidative stress was measured by the markers: glutathione (GSH) reductase, catalase, and superoxide dismutase activities as well as GSH, reactive oxygen species, and malondialdehyde levels. Gene and protein expression was detected by real-time polymerase chain reaction (PCR) and western blot, respectively. Results showed that MPH decreased 661 W cell viability, increased caspase-3/9 activities, and induced oxidative stress. Furthermore, MPH treatment increased messenger RNA (mRNA) expression of Beclin-1 and microtubule-associated protein 1A/1B-light chain 3B (LC3B) protein expression in 661 W cells, suggesting autophagy was induced. MPH treatment also upregulated p-JAK1/p-STAT1 protein expression. These data demonstrated that MPH could increase oxidative stress in photoreceptor cells to cause cell toxicity via autophagy, providing the scientific rationale for the photoreceptor cell damage caused by the MPH administration.